Impacto da conversão de floresta nativa em sistemas agrícolas nos compartimentos de carbono em solos do ecótono Cerrado-Amazônia - Bernadin, Ruthcatia (2021)
The conversion of native forests to agricultural systems is seen as the catalyst that, by compromising soil quality, leads to a rapid decline in soil carbon stocks. This work aimed to evaluate the carbon compartments in areas of native forest, agriculture and pasture in the Cerrado and Amazonia biomes, in the Amazon-Cerrado transition, totaling nine major study areas. This study was developed from soil samples collected at the Rio Ronuro Ecological Station (ESEC) located in the central region of the state of Mato Grosso in the municipality of Nova Ubiratã, characterized as Latossolo Vermelho-Amarelo. 216 samples were collected with 6 pseudo-repeats at depths from depths of 0,0-0,05m; 0,05-0,10m; 0,10-0,20m; 0,20-0,40m; 0,40-0,60m e 0,60-1,00m, at four points randomly along an imaginary path. In these samples, total C, labile C, chemical fractions of soil organic matter, humification index, soil organic matter lability and soil density were determined. The results showed that the removal of native areas for the introduction of agriculture reduced soil carbon stocks to a depth of 1.0 m, by 30% in the Cerrado, 33% in the Ecotone and 43% in the Amazon, after the period of 17 to 20 years of land use in relation to native vegetation. Changes in soil physical patterns (density) and chemical (CTC) were also observed, with further reductions of around 38% at a depth of 0.20m in Ecotone agriculture. There was a reduction in AF concentrations in the deepest layers of Biomes and Ecotone agricultural areas at a depth of 0.20 to 1.0 m. In addition, regardless of the Biome, it was found in the 0.0-0.05 m surface layer areas of native vegetation with higher values of carbon content (2,25%) and stocks (12.2 Mg ha-1 ) . However, pastures tend to show gains in carbon stocks, over the years due to the production of organic material with a high C/N ratio of grasses, reulting in recovery of soil organic matter quality.